Screening of antibacterial activity of endophytic fungi isolated from different leaf ages of curcuma mangga using different growth media - Mu’azzam, K.A.A.R; Taufiq, M.M.J.; Noor Azlina Ibrahim; Noorhazira; Darah Ibrahim (2015)
Endophytic fungi are microorganisms that resided symbiosis in whole or a part of its life-cycle in the living plant tissue without causing any disease symptoms to their host plant. Nowadays, the use of endophytes for antimicrobial activity is emphasized due to their ability to produce variety of novel secondary metabolites which are almost same to their host plant. The isolation of endophytic fungi from medicinal plants was believed to have significant use in pharmacology field since their growth can be manipulated and have potential to substitute the role of their host plant as a source of antibiotic compounds. Hence, in the present study, the endophytic fungi were isolated from different leave stages of medicinal herbs, Curcuma mangga using different growth media. The agar plug diffusion assay was implemented as primary screening for antimicrobial activity and followed by disc diffusion assay. A number of 142 endophytic fungi were isolated and the most of them succeed be isolated from senescent leaves using potato dextrose agar supplemented with host plant. In the primary screening, 66 (46.48%) isolates exhibited antimicrobial activity against test pathogenic microorganism and the percentage of isolates exhibiting antimicrobial activity increased due to increment of leaf age. The result suggested PDA agar medium with supplement of host plant powder and the healthy leaves at older growth stage can be potential source to isolate endophytic fungi from C. mangga leaves for their antimicrobial compounds.